Silencing JARID1B suppresses oncogenicity, stemness and increases radiation sensitivity in human oral carcinoma. Issue 1 (1st November 2015) - Lin, Chun-Shu; Lin, Ying-Chin; Adebayo, Bamodu Oluwaseun; Wu, Alexander; Chen, Jia-Hong; Peng, Yi-Jen; Cheng, Ming-Fang; Lee, Wei-Hwa; Hsiao, Michael; Chao, Tsu-Yi; Yeh, Chi-Tai
Highlights: JARID1B is overexpressed in oral squamous cell cancer (OSCC) tissue and cell lines. JARID1B modulates cell migration and invasion capability of the OSCCs. Silencing JARID1B disrupts OSCC stem cell-like characteristics. JARID1B positively modulates sensitivity of OSCC cell to radiotherapy. JARID1B is an independent predictor of disease survival. Abstract: Purpose: Oral squamous cell carcinoma (OSCC) is a major cause of human mortality globally and radiotherapy is one of the main treatment modalities, however its therapeutic effect is often limited by radioresistance. JARID1B is an epigenetic factor with reported oncogenic potential in various cancer types. We investigated the effect of JARID1B inhibition on migration and invasion of human OSCC cell lines, as well as on clinical patients' outcome. Materials and Methods: Wound healing, matrigel invasion, Sulforhodamine B, and spheroid formation assays were used to characterize the signaling pathways of shJARID1B in response to radiation treatment. We evaluated the prognostic relevance of Jarid1b expression in a cohort of 81 OSCC patients. Results: Human OSCC cell lines, including SAS, HSC3, Cal27, TW2.6 and SCC4 cells, were used. shJARID1B cells significantly inhibited migration and invasion ability compared to their vector or wild type counterparts. Silencing shJARID1B significantly inhibited oral cancer stem cell activity and potentiated the tumor-inhibitory activity of radiation therapy in OSCC. Radiotherapy coupled with shJARID1B knockdown reduced mRNA levels of NQO1, KEAP1, NRF2, FOXO1, FOXO3, KLF4, OCT4, CD133, and Nanog in malignant OSCC cells. OSCC spheroid formation ability was markedly reduced in the shJARID1B cells. JARID1B overexpression is a dependent prognostic factor in OSCC patients. Conclusions: Silencing shJARID1B inhibits migration and invasion of human OSCC, reduces cancer stem cell activities and potentiates tumor-inhibiting radiotherapeutic effects. JARID1B knockdown prior to radiotherapy is a potential effective therapeutic strategy for the treatment of OSCC.